The Apostolic Fathers: a revised text with introductions, notes, dissertations, and translations - Clement I, Pope.; Ignatius Saint, Bishop of Antioch, d. ca. 110.; Polycarp Saint, Bishop of Smyrna.; Lightfoot, Joseph Barber (Macmillan, 1889)
pt. 1, v. 1-2. S. Clement of Rome.--pt. 2, v. 1-3. S. Ignatius; S. Polycarp.